Use of Cefadroxil For American Tegumentary Leishmaniosis With Intercurrent Pyogenic Infections - Pedro Navarro; Sylvia Silva; María De la Parte; Luis Alfonso Colmenares; Virginia Coraspe; Elinor Garrido; María Redondo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Cutaneous leishmaniosis of the New World (CLNW) is a health problem in rural areas of Venezuela. Patients with muco-cutaneous ulcers tend to present intercurrent infections of the lesions by pyogenic bacteria. After removing skin specimens from the ulcer borders for microscopic demonstration of Leishmania spp amastigotes, forty-one patients with the disease, being treated with cefadroxil per os were studied. Most of the patients came from rural Miranda state, were male adults and had one ulcer on a lower limb. Confirmatory diagnosis was made using the Montenegro test, or Leishmanin immunoserology (IFAT) and demonstration of the presence of parasites in the skin samples. All the patients were positive for the Leishmanin test, while parasites were observed in 51% of the skin smears colored by the Giemsa procedure. After a week of treatment with cefadroxil, bacterial infections were reduced and a decrease in bacterial load was also noted when visualizing the parasite from the skin smears. Patients were treated with intramuscular antimony meglumine for 10-day periods with an intervening rest period. All patients responded adequately to the meglumine antileishmania treatment; the lesions healed and accompanying tributary lymph nodes disappeared. Conclusion: Cefadroxil is a suitable antibiotic for treating intercurrent pyogenic infections in cases of tegumentary leishmaniosis. Since leishmaniosis is considered an emerging disease, a search for appropriate, alternative therapies is required.